2017
DOI: 10.1186/s12890-017-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare burden of pulmonary hypertension owing to lung disease and/or hypoxia

Abstract: BackgroundGroup 3 pulmonary hypertension (PH) encompasses PH owing to lung diseases and/or hypoxia. Treatment patterns, healthcare resource use, and economic burden to US payers of Group 3 PH patients were assessed.MethodsThis retrospective observational study extracted data from July 1, 2010 to June 30, 2013 from two Truven Health Analytics MarketScan databases. Adult Group 3 PH patients were identified based on claims for PH (ICD-9-CM 416.0/416.8), a related lung disease, and an echocardiogram or right heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The likely elevation of healthcare utilisation in patients with ILD arises in part from comorbidities in patients with ILD that include cardiovascular disease, malignancy, sleep apnoea and pulmonary hypertension (PH), and contribute to hospitalisations, physician visits and medication use [6,49,50]. Again, using the example of IPF, in a recent analysis of healthcare costs and utilisation in patients covered by Medicare in the USA, it was estimated that the total annual medical costs in 2000-2011 were up to USD 3 billion, of which USD 1.8 billion was attributable to IPF and associated comorbidities [13].…”
Section: Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The likely elevation of healthcare utilisation in patients with ILD arises in part from comorbidities in patients with ILD that include cardiovascular disease, malignancy, sleep apnoea and pulmonary hypertension (PH), and contribute to hospitalisations, physician visits and medication use [6,49,50]. Again, using the example of IPF, in a recent analysis of healthcare costs and utilisation in patients covered by Medicare in the USA, it was estimated that the total annual medical costs in 2000-2011 were up to USD 3 billion, of which USD 1.8 billion was attributable to IPF and associated comorbidities [13].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Again, using the example of IPF, in a recent analysis of healthcare costs and utilisation in patients covered by Medicare in the USA, it was estimated that the total annual medical costs in 2000-2011 were up to USD 3 billion, of which USD 1.8 billion was attributable to IPF and associated comorbidities [13]. For example, World Health Organization group 3 PH is associated with substantially higher healthcare resource use than in control disease-matched patients, particularly in the number of prescription claims, outpatient visits and physician office visits [49]. Prevalence rates of comorbidities in IPF have been published with wide ranges, for example: PH 8-84%; cardiac disease 60%; lung cancer 4.4-10%; and sleep apnoea, 60-90% [49,50].…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Nonetheless, studies have shown a significant number of these patients do receive PAH-targeted therapies 44,45 and the need to evaluate therapies in groups 2 and 3 has been highlighted. 4447 We have demonstrated that the ISWT is a useful tool for assessing exercise capacity for clinical monitoring and may have utility as an endpoint in trials of targeted therapies for non-group 1 PH.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating inhaler use among older adults with chronic obstructive pulmonary disease and/or asthma, Castaldi and colleagues noted that an OOP expense greater than $20 per month was associated with costrelated nonadherence to inhaler therapy compared with patients with no OOP inhaler costs (11). Another study found that among patients with group 3 pulmonary hypertension, prescription medication comprised 33% of healthcare spending, second to inpatient hospitalizations (35.4%) but more than the 26.5% attributed to outpatient care (12). Although pharmacy benefit managers can help patients with IPF manage the high cost of medications such as nintedanib and pirfenidone (13), to date there are no published studies evaluating how the costs of IPF medications directly affect patients and their families.…”
Section: Financial Toxicity: a Side Effect For Many Patientsmentioning
confidence: 99%